MODEL OF REJUVENATION OF OIL PALM PLANTATIONS BASED ON COMMUNITY EMPOWERMENT ON TRANSMIGRANT FARMERS' LAND - Endang Solichin; Mardalena Mardalena; Nugroho Nugroho (Dinasti International Journal of Education Management And Social Science, 2020)
Empowerment of the weak economic community is an effort to enable and empower the community. transmigration is a model of population distribution as well as an effort to improve the welfare of the economically weak community in the agricultural sector. The purpose of this study was to examine the model of rejuvenation of oil palm plantations based on community empowerment on oil palm land owned by transmigrants in Pulau Tujuh village, Mampun Village and Rasau Village, Pamenang Barat District, Merangin District, Jambi Province. The focus of this research is the model of rejuvenation of community empowerment-based oil palm plantations on oil palm farms belonging to transmigrant farmers in Pulau Tujuh village, Mampun Village and Rasau Village, West Pamenang District, Merangin District, Jambi Province.The methods used in this study were interviews, observations and discussions with oil palm farmers transmigrants in the village. The results of the study found a model for the rejuvenation of oil palm plantations based on the empowerment of migrant oil palm farmers by combining three main forces, namely the Fund Provider, Core People, Plasma and Government companies, in the form of Four point Zero in Pulau Tujuh Village, Mampun Village and Rasau Village Pamenang District West Merangin district.